The influence of the interlayer on the magnetic and structural properties of three-layer systems. (November 2019) - Shalygina, E; Kharlamova, A; Efremova, S; Makarov, A; Kurlyandskaya, G; Svalov, A
Abstract: This article is dedicated to the influence analysis of the thickness and composition of nonmagnetic intermediate layers, t NM, on the magnetic and structural properties of Co/Mo/Co, Co/Si/Co, Co/Bi/Co and Fe1 /PDP/Fe2 thin-film systems, as well as comparing the mechanisms of exchange interaction between ferromagnetic, FM, layers through NM spacers. The thicknesses of Co layers are equal to 5.0 nm and the thickness of Fe layers is varied from 14.0 to 50.0 nm. The thickness of NM layers, depending on its composition, is changed from 0.2 to 50.0 nm. It is found that the hysteresis loops for some samples measured in a magnetic field applied parallel to the easy magnetization axis have a rectangular form and for others – more complex two-step ones. The saturation field, H S, of Co/Mo/Co, Co/Si/Co and Co/Bi/Co samples oscillates in magnitude. These data are explained by the presence of exchange coupling between the Co layers through a NM spacer. Fe1 /PDP/Fe2 samples have a two-step hysteresis loops, which at t PDP ≥ 10 nm are explained by the exchange coupling between the Fe layers through the PDP layer, and at t PDP > 10 nm - by the magnetostatic interaction between the Fe layers due to the difference in their thickness.